Fibroblast growth factor 16 stimulates proliferation but blocks differentiation of rat stem Leydig cells during regeneration. Issue 4 (22nd January 2019) - Duan, Yue; Wang, Yiyan; Li, Xiaoheng; Mo, Jiaying; Guo, Xiaoling; Li, Chao; Tu, Mengyan; Ge, Fei; Zheng, Wenwen; Lin, Jing; Ge, Ren‐Shan
Abstract: Objectives: We aim to investigate the effects of fibroblast growth factor 16 (FGF16) on Leydig cell regeneration in ethane dimethane sulphonate (EDS)‐treated rat testis. Methods: We intraperitoneally inject 75 mg/kg EDS to adult male Sprague Dawley rats and then intratesticularly inject FGF16 (0, 10 and 100 ng/testis/day) from post‐EDS day 14 for 14 days. We investigate serum hormone levels, Leydig cell number, gene and protein expression in vivo. We also explore the effects of FGF16 treatment on stem Leydig cell proliferation in vitro. Results: FGF16 lowers serum testosterone levels (21.6% of the control at a dose of 100 ng/testis) without affecting the levels of luteinizing hormone (LH) and follicle‐stimulating hormone (FSH) on post‐EDS day 28 in vivo. FGF16 increases Leydig cell number at doses of 10 and 100 ng/mg without affecting Sertoli cell number, increases the percentage of PCNA‐positive Leydig cells, and down‐regulates the expression of Leydig cell genes ( Lhcgr, Scarb1, Star, Cyp11a1, Cyp17a1 and Hsd17b3 ) and Sertoli cell genes ( Fshr, Dhh and Sox9 ) and their proteins in vivo. FGF16 increases phosphorylation of AKT1 and AKT2 as well as EKR1/2 in vivo, indicating that it possibly acts via AKT1/ATK2 and ERK1/2 pathways. FGF16 also lowers medium testosterone levels and down‐regulates the expression of Leydig cell genes ( Lhcgr, Scarb1, Star, Cyp11a1, Cyp17a1 and Hsd17b3 ) but increases EdU incorporation into stem Leydig cells in vitro. Conclusions: These data suggest that FGF16 stimulates stem and progenitor Leydig cell proliferation but blocks their differentiation, thus lowering testosterone biosynthesis.